Biomimetic 4D printed materials: A state-of-the-art review on concepts, opportunities, and challenges. (2021) - Ayushi,; Kumar Vates, Umesh; Mishra, Sanjay; Jee Kanu, Nand
Abstract: The additive manufacturing is a transformative technique which improves the mechanical properties, e.g., the strength of the fabricated light weight industrial products. CAD softwares are integrated in the rapid prototyping setup and fabrication of the product is done through bottom-to-top approach via layer-wise deposition using stereo lithography file format as input. The 4D printed biomimetic materials are having shape changing capabilities, i.e., stimuli responsive features such as heat and thermal sensitivity, electromagnetic sensitivity, so, and so forth, as that comes under the fourth dimension. 4D printing is not just the extended technique of 3D printing but also the manufacturing technique of fabricating complex three-dimensional objects which can change the shape and forms when they are exposed to external environmental stimuli. 4D printing is appending one more dimension in the 3D printing, i.e., time. The review paper covers all aspects related to shape changing mechanisms from conceptual to actual design and emphasize has been given to the modern advancements in biomimetic 4D printing and sustainable biomedical and environmental applications.